Exercise induced dehydration status and skinfold compressibility in athletes: An intervention study - Araújo, D (2018)
Background and Objectives: Skinfold thickness assessment is a widely recognized technique for the estimation of body adiposity and fat free mass. This method assumes that skinfolds' compressibility is constant but there are some factors that could influence its compressibility. This study aims to evaluate whether the skinfolds' compressibility is influenced by hydration status. Methods and Study Design: An intervention study was conducted in a sample of 22 adult male amateur soccer players, who took part in a 90min simulated soccer match. Before and after the intervention skinfolds thicknesses were measured in eight anatomical sites. An electronic caliper, Lipotool, was used to collect and record 120 values during 2s of evaluation. To analyze skinfolds' compressibility, two methods were used: identification of lowest skinfold thickness measurement (SL) and SH = 110% x SL, and the parameter TAU () determination. Baseline hydration status was evaluated by total body water (TBW) through multifrequency bioimpedance analysis. Dehydration was assessed by the difference of body weight before and after the intervention. Results: The intervention resulted in a loss of 2.11% of participants' baseline weight. The skinfolds thicknesses, assessed by SL and SH, were significantly higher after exercise for all skinfolds except for skinfolds at iliac crest and abdominal. This intervention did not affect skinfolds' compressibility when assessed by . However, an association between dehydration and medial-calf skinfold' compressibility was found (r=0.48, p=0.042). Conclusions: Although an increase in the skinfolds thickness after the intervention was found, skinfolds' compressibility did not change.